Homologous MXene‐Derived Electrodes for Potassium‐Ion Full Batteries. Issue 23 (11th May 2022) - Sun, Lanju; Sun, Jikai; Zhai, Shengliang; Dong, Tiantian; Yang, Hongyan; Tan, Yi; Fang, Xu; Liu, Chengcheng; Deng, Wei‐Qiao; Wu, Hao
Abstract: The development of potassium‐ion battery (PIB) electrode materials is critical for promoting their use in next‐generation energy storage systems. Although metal–organic frameworks (MOFs) are appealing electrode materials, their performance in PIBs remains unsatisfactory. The low K + adsorption energy (Δ E a ) on the saturated coordination of MOFs can explain the limited capacity. Herein, MXene‐derived MOF nodes (NMD‐MOF) are unlocked and used as anodes in PIB. The NMD‐MOF anode exhibits substantially increased capacity (250 mA h g −1 at 0.05 A g −1 ), as well as good rate‐performance and excellent capacity retention. Density functional theory calculations reveal that the Δ E a at unlocked node sites is significantly higher than at intact node sites of the pristine MOF. Furthermore, the NMD‐MOF anode and homologous MXene‐derived K + ‐intercalated vanadium oxide (MD‐KVO) cathode combine to assemble a PIB, which delivers an encouraging capacity of 63 mA h g −1 at 50 mA g −1 and high energy (143 Wh kg −1 ) and power density (440 W kg −1 ). The fabrication of MXene‐derived electrode materials and the unlocking node strategy for binding site activation may spur further research into highly active electrode materials for energy storage devices. Abstract : A potassium ion full battery is assembled with a homologous MXene‐derived metal–organic framework (MOF) anode and K + ‐intercalated vanadium oxide cathode. Meanwhile, an unlocking MOF node strategy is proposed to increase the K + adsorption energy, which leads to significantly improved K + storage capacity.